Soil carbon and nitrogen mineralization under different tillage systems and Permanent Groundcover cultivation between Orange trees - Elcio Liborio Balota; Pedro Antonio Martins Auler (Revista Brasileira de Fruticultura, 2011)
The objective of this work was to evaluate the alterations in carbon and nitrogen mineralization due to different soil tillage systems and groundcover species for intercropped orange trees. The experiment was established in an Ultisol soil (Typic Paleudults) originated from Caiuá sandstone in northwestern of the state of Paraná, Brazil, in an area previously cultivated with pasture (Brachiaria humidicola). Two soil tillage systems were evaluated: conventional tillage (CT) in the entire area and strip tillage (ST) with a 2-m width, each with different groundcover vegetation management systems. The citrus cultivar utilized was the 'Pera' orange (Citrus sinensis) grafted onto a 'Rangpur' lime rootstock. The soil samples were collected at a 0-15-cm depth after five years of experiment development. Samples were collected from under the tree canopy and from the inter-row space after the following treatments: (1) CT and annual cover crop with the leguminous Calopogonium mucunoides; (2) CT and perennial cover crop with the leguminous peanut Arachis pintoi; (3) CT and evergreen cover crop with Bahiagrass Paspalum notatum; (4) CT and cover crop with spontaneous B. humidicola grass vegetation; and (5) ST and maintenance of the remaining grass (pasture) of B. humidicola. The soil tillage systems and different groundcover vegetation influenced the C and N mineralization, both under the tree canopy and in the inter-row space. The cultivation of B. humidicola under strip tillage provided higher potential mineralization than the other treatments in the inter-row space. Strip tillage increased the C and N mineralization compared to conventional tillage. The grass cultivation increased the C and N mineralization when compared to the others treatments cultivated in the inter-row space.